Physical boundaries within aggregates – differences between amorphous, para‐crystalline, and crystalline Structures. Issue 11 (3rd August 2015) - Albers, Peter; Maier, Monika; Reisinger, Martin; Hannebauer, Bernd; Weinand, Rudolf
Abstract : The macro‐ and micro‐morphological properties of commercially available oxide powders in common use are determined as received and after dispersing to the level of the smallest compact structures. Grain‐ and phase‐ boundaries observed in the aggregates of crystalline materials are completely absent in amorphous synthetic silica and para‐crystalline carbon black. In these cases the aggregate is the constituent particle. Abstract : The structural properties of finely divided inorganic materials such as metal and metalloid oxides, silicates or carbonates of both synthetic and natural origin are compared by means of electron microscopy and tomography. The structure of the outer surfaces of various compact or compacted agglomerates may suggest some striking similarities between various amorphous silica on the one hand and crystalline titania and alumina on the other however the details of the interior fine structure are completely different. Inside of the crystalline aggregates of, for example, alumina and titania distinct grain boundaries between the inter‐grown primary crystallites exist. Also physical boundaries between different solid phases and crystalline/amorphous transitions in core/shell structures can occur. No physical grain or phase boundaries were found inside of synthetic amorphous silica or para‐crystalline carbon black thus, the aggregate is the constituent particle. Synthetic amorphous silica from different production technologies (fumed/pyrogenic, precipitated, aerogel, gel) may exhibit different macro‐morphology but distinct similarities of the amorphous silica networks. Computational studies on silica and titania underline the stability of constituent particles and aggregates as observed by means of TEM after dispersing the original materials by ultra‐sonication.